A CRIMINAL LEGAL PROTECTION OF THE ENVIROMENT IN THE REPUBLIC OF MACEDONIA - Kalac, Yasmin (International Scientific Journal Vision, 2017)
The environmental and nature protection in which man lives and works as an individual is one of the most important and most complex problems in the world. Since the very human existence the environment is the primary condition and necessity for its existence. Considering the fact that the environment is endangered and therefore human health, through the enormous industry and technology development, is required more serious and more effective preventive role by the competent authorities in relation to criminal legal protection of the environment. In this paper I will try to give an overview of the way that criminal legal protection of the environment is regulated under the legislation of the Republic of Macedonia.